THE SPECIFIC FEATURES OF SPEECH THERAPY GAMES IN SPEECH DISORDERS - Maxmudova Madinaxon Sobirxonovna; Meliko’ziyeva Fotimaxon Sobitjon qizi (Bright Mind Publishing, 2025)
This article systematically covers the specific features of speech therapy games in speech disorders. The article describes in detail the games organized for children with speech disorders during speech therapy sessions, the theory of special education, creative games and games with rules.
Keywords: Speech, development, game, early childhood, child, baby, sound, word, communication, language, speech stages, speech formation, creative game, game with rules.